PENGARUH KOMITMEN ORGANISASI, PENGAWASAN FUNGSIONAL DAN PENGENDALIAN INTERN TERHADAP KINERJA PEMERINTAH DAERAH (Studi Empiris pada SKPD Kabupaten Kuantan Singingi) - Lidia Hasnani; Taufeni Taufik; Eka Haryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine organizational commitment, functional supervising and government's internal control system toward performance of local governments. The population in this study is SKPD in Kabupaten Kuantan Singingi. The sample selections using total sampling, with 50 respondents. The data used in this study in the form of primary data. The data of this study was collected by using survey techniques, where the researcher distributed questionnaires to each SKPD’s chairman and chief of financial SKPD. The technique of data analysis used multiple regression analysis by using Statistical Package for Social Science (SPSS) program. This research proves that the organizational commitment bring a significanton performance of local governments with regression coefisient 0,231 and significant value 0,042 (alpha 0,05), this is shown by the result of tcount 2,088 which is higher than the ttable 2,000. Functional supervising bring significantion performance of local governments with regression coefisient 0,202 and significant value 0,026 (alpha 0,05), this is shown by the result of tcount 2,308 which is higher than the ttable 2,000. Government’s internal control systems bring significanton performance of local governments with regression coefisient 0,131 and significant value 0,041 (alpha 0,05), this is shown by the result of tcount 2,098 which is higher than the ttable 2,000.Keywords: Organizational Commitment, Functional Supervising, Internal Control System and Performance of Local Governments.